PWE-010 Radiofrequency ablation (rfa) is safe and effective for the treatment of gastric antral vascular ectasia refractory to apc – results of a national audit. (22nd June 2015) - Dunn, JM; Boger, P; Cheong, E; Fullard, M; Leahy, A; Murphy, T; Smart, H
Abstract : Introduction: Gastric antral vascular ectasia (GAVE) is a cause of upper GI bleeding and chronic anaemia. Argon plasma coagulation (APC) is considered first line therapy for GAVE, although technique is variable and evidence for long term treatment success is lacking. Radiofrequency ablation (RFA) may provide an alternative therapeutic option for GAVE, due to controlled depth of ablation and ability to treat a wider field. Method: Retrospective audit of patients with GAVE treated with RFA at 6 UK HALO registry centres, over an 18 month period (August 2013–Feb 2015). Patients were treated with an RFA Ultra 90 (at 12J x3), RFA 90 (at either 12J x4 or 15J x 3) or Channel device (12J x3). A no clean technique was used to minimise bleeding. End points were transfusion requirements post ablation, clinical response and endoscopic response. Results: A total of 15 patients were treated, 60% female. Average age was 69 years (range 35–89 years). Aetiology was idiopathic 53%, cirrhosis/NASH 20%, Cardiac/renal disease 20%, Scleroderma 7%. A total of 216 Units of blood were transfused in the 6 months prior to RFA (median 2 per month pre RFA). Patients received a median of 2 treatment sessions 3 months apart. Two patients died during the follow up phase unrelated to RFA. A mean of 42 ablations were used at first session, and 67 at subsequent sessions. Transfusion requirements fell significantly for all patients post RFA, with 13/17 requiring no transfusion after a mean follow up of 2 months (range 1–6). Median number of transfusions was 12 (IQR 5–24) pre RFA vs. 0 (IQR 0–7) post RFA (paired t-test p < 0.001). Mean Hb prior to RFA was 73 g/l, post RFA was 97 g/l. The majority of patients achieved clinical response (87%), with 20% achieving complete endoscopic response. Conclusion: This national audit of practice demonstrates Radiofrequency Ablation is safe and effective for the treatment of GAVE refractory to APC. Significant reductions in transfusion requirements and clinical response were achieved. A national prospective study, with a standardised protocol and long term follow up, is warranted for this promising new technique. Disclosure of interest: None Declared.